الإسلاموفوبي، معنى الجهاد و الاستراتيجيتها على حماية المسلمين - Muhammad Agus Sofian (Raudhatun Najah Publisher, 2022)
This writing aims to explain Islamophobes and protect Muslims over the people in the world, becoming Islamophobes not transforming the model and goals of Islam itself. Then get it from people in the world who hate and fear Islam and yet most Western politicians deal with this phenomenon. This study also supports the theory of scholars and thinkers on Islamophobia and its protection from Muslims and how to deal with it. This study uses a qualitative method, which is research with desk research models. The primary sources that the researcher used are the Quranic verses about the true meaning of the word